Analisis Nilai CAR , LDR Dan NPL Pada Nilai ROA LPD Desa Adat Penglatan - I Gede Rizki Widana; Made Dwi Ferayani (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract At the analysis stage of the CAR value. However, the researcher applies the data sourced from the LPD financial statements, namely by using a quantitative approach. In observing the data, an evaluation tool is needed, namely using multiple linear analysis by conducting the analyzer so that it can find out the strong relationship related between each variable and provide an explanation of the effect simultaneously and then partially test with the aim of knowing the impact given by the independent variable, namely CAR, NPL to dependent ROA. After knowing the results of data management, the next step is to measure the construct test through coefficients by obtaining an R square relationship of 34.4% LPD ROA value resulting from the independent variable. The next step is the simultaneous test if the CAR, LDR, and NPL values ​​on ROA get results together and will have a positive impact on the Roa variable. then through the T test, it was found that the CAR value had a positive and insignificant effect on ROA, LDR was able to provide a positive relationship but did not meet the standard p value on ROA and the effect of NPL on ROA had positive and insignificant results. Keywords: CAR, LDR, NPL,ROA